Penerapan User Centered Design Pada Desain Interaksi dan Arsitektur Informasi Prototype Aplikasi Asisten BasketMu - Raden Kartika Satya; Dimas Sasongko; Setiya Nugroho; Ridwan Anam Syabani; Raka Putra Anggarawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Coaches have a very important role in the achievements of sports athletes. The coach has the responsibility to organize training methods that suit the athlete's needs and goals. Coaches generally record the performance of team members during training. Recording athlete performance can be used to measure athlete development and improve athlete abilities. Based on the results of interviews and observations with several basketball coaches, they still record on paper forms. The main contribution of this research is to produce an application design that has an information architecture and interaction model to help improve the coach's user experience in recording and monitoring anthropometric developments, physical development, and athlete skill development during training and recording player statistics during matches. Apart from recording the resulting application, it is hoped that it can improve the user experience of coaches and players in analyzing performance data during training and matches. This research uses the User Centered Design method. This research has produced a prototype in high fidelity form. Based on functionality testing using the black box testing method, it shows that the prototype feature can be successful as expected. The User Experience test results show that the average Task Success value from testing the player's user interface is 77%, while the average Task Success value from testing the trainer's user interface is 82%.